Dental abscess in a tooth with intact dens evaginatus - S. Y. CHO (Paediatric Dentistry, 2006)
Dens evaginatus is a developmental anomaly that can be defined as a tubercle from the surface of an affected tooth and is found most frequently in premolars [1,2].